Efficiency of Monitoring Household Electricity With ZMCT103C - Suteja, I Wayan Arsa; antara, adi surya; Wiantara Putra, Gede Eka; Putu, Ida Bagus (Patria Artha Technological Journal, 2023)
An electric load monitoring system is a tool designed to monitor and measure electricity usage. The process of monitoring the electrical load uses a current sensor model ZMCT103C which is connected to the electrical load. The microcontroller used is an Arduino Uno microcontroller which functions as the main control system which will be connected to a 16x2 LCD monitor with the aim that in the future it can be monitored in real time and can be read directly on the LCD. By carrying out experiments on assembling the ZMCT103C sensor module with Arduino Uno which produces a monitoring feature for current measurement readings. The result of this research is a household electricity measurement monitoring system through a prototype made using the ZMCT103C sensor model with an Arduino Uno which is equipped with a 16x2 LCD monitor to make it easier to monitor the electrical energy load from household electronic devices in the form of current readings. The magnitude of the current measurement obtained from the reading of the ZMCT103C model current sensor will be compared to the ampere meter measuring instrument. By conducting this research, we can obtain data on the percentage of error obtained from the application of the ZMCT103C sensor, so that later from the results of this experiment the ZMCT103C sensor will be able to properly and correctly monitor electricity usage for household loads.